The Sec1/Munc18‐like proteins TgSec1 and TgVps45 play pivotal roles in assembly of the pellicle and sub‐pellicle network in Toxoplasma gondii. Issue 1 (19th November 2019) - Cao, Shinuo; Chen, Heming; Liang, Xiaohan; Fu, Jiawen; Wang, Shida; Zheng, Jun; Zhang, Zhaoxia; Pang, Yu; Wang, Jingfei; Shen, Bang; Jia, Honglin
Summary: Post‐Golgi vesicle trafficking is indispensable for precise movement of proteins to the pellicle, the sub‐pellicle network and apical secretory organelles in Apicomplexa. However, only a small number of molecular complexes involved in trafficking, tethering and fusion of vesicles have been identified in Toxoplasma gondii . Consequently, it is unclear how complicated vesicle trafficking is accomplished in this parasite. Sec1/Munc18‐like (SM) proteins are essential components of protein complexes involved in vesicle fusion. Here, we found that depletion of the SM protein TgSec1 using an auxin‐inducible degron‐based conditional knockout strategy led to mislocalization of plasma membrane proteins. By contrast, conditional depletion of the SM protein TgVps45 led to morphological changes, asymmetrical loss of the inner membrane complex and defects in nucleation of sub‐pellicular microtubules, polarization and symmetrical assembly of daughter parasites during repeated endodyogeny. TgVps45 interacts with the SNARE protein TgStx16 and TgVAMP4‐1. Conditional ablation of TgStx16 causes the similar growth defect like TgVps45 deficiency suggested they work together for the vesicle fusion at TGN. These findings indicate that these two SM proteins are crucial for assembly of pellicle and sub‐pellicle network in T. gondii respectively. Abstract : TgSec1, a Sec1/Munc18‐like protein, is essential for the plasma membrane protein trafficking in T. gondii . TgVps45 is required for the vesicle transport of inner membrane proteins and nucleation of sub‐pellicular microtubules during assembly of daughter parasites. TgStx16 (Qa), a TgSNARE protein, interacted with TgVps45 (SM) and TgVAMP4‐1 (R) and participated in vesicle transport from TGN in T. gondii.